2022
DOI: 10.1101/2022.11.06.515380
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Whole-cortex in situ sequencing reveals peripheral input-dependent cell type-defined area identity

Abstract: The cortex is composed of neuronal types with diverse gene expression that are organized into specialized cortical areas. These areas, each with characteristic cytoarchitecture1–3, connectivity4,5, and neuronal activity6–10, are wired into modular networks4,5,11. However, it remains unclear whether cortical areas and their modular organization can be similarly defined by their transcriptomic signatures. Here we used BARseq, a high-throughput in situ sequencing technique, to interrogate the expression of 107 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 102 publications
2
26
0
Order By: Relevance
“…Our in situ sequencing approach is based on BARseq, a high-throughput technique that can determine both long-range projections of neurons and their gene expression by in situ sequencing of both endogenous gene expression and an mRNA barcode encoded in the genome of Sindbis virus (Chen et al ., 2019; Sun et al ., 2021). We have previously shown that BARseq-style in situ sequencing can distinguish transcriptomic types of cortical neurons with high transcriptomic resolution in a uninfected mouse brain (Chen et al ., 2022a). To adapt BARseq to rabies barcodes ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our in situ sequencing approach is based on BARseq, a high-throughput technique that can determine both long-range projections of neurons and their gene expression by in situ sequencing of both endogenous gene expression and an mRNA barcode encoded in the genome of Sindbis virus (Chen et al ., 2019; Sun et al ., 2021). We have previously shown that BARseq-style in situ sequencing can distinguish transcriptomic types of cortical neurons with high transcriptomic resolution in a uninfected mouse brain (Chen et al ., 2022a). To adapt BARseq to rabies barcodes ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In situ sequencing oligos RT primers, sequencing primers, and padlock probes for both endogenous genes and rabies transcripts are designed as previously described (Sun et al, 2021;Chen et al, 2022a). A list of oligos used in in situ sequencing are provided in Table S3.…”
Section: Viruses and Constructsmentioning
confidence: 99%
See 2 more Smart Citations
“…We propose that in AD, the selective vulnerability of the DMN is a consequence of intrinsic vulnerability to injury and is not explained by the anatomical specificity of amyloid accumulation. Within DMN regions, the vulnerability of individual neurons to functional disruption is like to be determined by the gene expression underlying connectivity patterns (Whitesell et al, 2021; Chen et al, 2022). The advent of new technologies in measuring mesoscale connectivity, recording neuronal activity, and resolving spatial transcriptomics will make it possible to further disentangle to cellular and circuit rules disease spread through the DMN.…”
Section: Discussionmentioning
confidence: 99%